PREVALENCE OF PREHYPERTENSION AND HYPERTENSION AND THEIR ASSOCIATION WITH BODY MASS INDEX IN YOUNG FEMALE ADULTS OF HYDERABAD, PAKISTAN.: JPUMHS;2024:14:04,139-144 .http://doi.org/10.46536/jpumhs/2024/14.04.571 - Muhammad Zaman Baloch1, Jaweria Amjad Memon2, Ayaz Ali Samo3, Nimra Masood Baig4, Hajra Naila5, Zulfiqar Ali Laghari6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Prevalence of prehypertension and hypertension has been reported as the cause of concern among young females. Higher blood pressure can have adverse outcomes among females. The increase in the prevalence of overweight and obesity has been the major factor for the increase in systolic and diastolic blood pressure. BMI has been used to measure overweight and obesity. This study is focused on the prevalence of prehypertension and hypertension among young female adults who are residing in Hyderabad, Pakistan. This study was conducted in female adults in the selected areas of Hyderabad Pakistan. The data was obtained by interview-based questionnaire. The data was collected only during the morning timing from 8.30 am to 10.30 am to have consistency in the data, the weight and height were measured as the standard protocols using the weight in kilograms and height in centimeters. BMI was calculated for the subjects using the standard formula. The Blood pressure was measured using the sphygmomanometer. The data was analyzed using the statistical software SPSS 22. All the ethical measures were kept into consideration before the collection of the data. Prevalence of hypertensions was higher 36% followed by hypertension 7.8% among the studied female subjects. The prevalence of hypertension was 17.6%and the prevalence of prehypertension was 27.2%. The prevalence of prehypertension and hypertension was significantly higher χ=1.78, P < 0.05 among the overweight and obese female adults. Similarly the BMI showed a positive significant correlation with both SBP r=0.401, P < 0.001 and DBP r= 0.443, P < 0.001. This study concludes the higher prevalence of prehypertension and hypertension among young female adults. The BMI showed a positive correlation with SBP and DBP. This is alarming and further study is needed to find out the intervention strategies. This study will help in making public health policies